2011
DOI: 10.1007/978-3-642-24469-8_26
|View full text |Cite
|
Sign up to set email alerts
|

Multilingual Adaptive Search for Digital Libraries

Abstract: Abstract. This paper describes a framework for Adaptive Multilingual Information Retrieval (AMIR) which allows multilingual resource discovery and delivery using on-the-fly machine translation of documents and queries. Result documents are presented to the user in a contextualised manner. Challenges and affordances of both Adaptive and Multilingual IR, with a particular focus on Digital Libraries, are detailed. The framework components are motivated by a series of results from experiments on query logs and doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Several authors have observed that the development of methodologies and tools supporting multilingual information discovery is essential to make non-English content available to end users [8], [12], [15]. Gohrab [8] proposes a framework that performs on-the-fly machine translation of queries and documents.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have observed that the development of methodologies and tools supporting multilingual information discovery is essential to make non-English content available to end users [8], [12], [15]. Gohrab [8] proposes a framework that performs on-the-fly machine translation of queries and documents.…”
Section: Related Workmentioning
confidence: 99%
“…Gohrab [8] proposes a framework that performs on-the-fly machine translation of queries and documents. This framework does not rely on controlled vocabularies, but supports automatic translation of queries using external services like "Google Translate 6 " or "Microsoft Translator 7 ".…”
Section: Related Workmentioning
confidence: 99%